RESTORASI PRAKTEK PENGALAMAN LAPANGAN (Studi Inovasi Manajemen Kurikulum PPL melalui Kolaborasi Pendekatan Craft, Competency dan Reflective Model) - Mustaqim, Mujahidil (Prodi Teknologi Pendidikan, 2017)
Abstract. This article is based on the fact that until now there has not been any serious at-tempt to improve field experience practice (PPL). This was indicated by a number of common problems that occur surrounding fiend experience practice, such as inability to maximally meet the goals of the program, ambiguity of supervisor teachersâ€™ job description in educating student teachers, and loose and asymmetrical coordination between teachers college (LPTK) as producer and schools as industry. Thus, there needs to be restoration of field experience practice which is initiated by establishing PPL curriculum management which collaborates Craft, Competency and Reflective Models. This article presents three principal suggestions, which were obtained from literature study and data collection from observation and interview. First, there should be design innovation of PPL curriculum management using Craft, Competency and Reflective Models ap-proach by formulating success criteria and instructional plan of the program to be used as guid-ance of supervisor teachers in educating student teachers. In so doing, there will be change in the process of educating the students which is usually accidental instead of as planned. Second, it is important to formulate elaborate job description of supervisor teacher during introduction, train-ing, and evaluation periods based on the common problems that usually occur so that the role of the supervisor teacher can be optimized, which will impact the studentsâ€™ teaching competency. Third, there should be simultaneous, continuous, and intensive coordination between teachers college (LPTK) and schools in order to create symbiotic relationship in establishing prospective professional future teachers.Keywords: field experience practice, curriculum management, teacher education model, Craft, Competency and Reflective ModelsAbstrak. Artikel ini didasari atas seputar distorsi praktek pengalaman lapangan (PPL) namun hingga kini belum benar-benar tersentuh oleh iktikad perbaikan. Hal ini tampak dari sepu-tar realitas lazim antara lain pada beberapa kasus disebutkan bahwa belum maksimalnya pen-capaian tujuan PPL, ketaksaan kerangka kerja (job description) guru pamong dalam mendidik ma-hasiswa PPL, dan koordinasi yang masih dinilai belum erat dan simetris antara Lembaga Pendidi-kan dan Tenaga Kependidikan (LPTK) sebagai produsen dan sekolah sebagai industri. Maka untuk menangani persoalan ini, maka perlunya restorasi kegiatan PPL sehingga kompetensi lulusan kegiatan PPL dapat lebih terstandar dari sebelumnya dan tujuan PPL dicapai dengan optimal. Selain itu, kegiatan PPL dapat memberi makna khusus dan manfaat yang mendalam bagi calon guru sebelum terjun ke dunia kerja. Sehingga, kesan yang selama ini masih berbekas bahwa guru baru tidak â€œwell preparedâ€ saat memasuki dunia mengajar tidak lagi muncul. Hal ini dapat tercapai dengan menginisiasi tiga hal berikut, yaitu: Pertama, perlunya sebuah inovasi yakni mendesain manajemen kurikulum PPL menggunakan pendekatan craft, competency, dan reflective model me-lalui perumusan kriteria keberhasilan PPL dan rencana pembelajaran PPL yang dimakudkan men-jadi pedoman bagi guru pamong dalam mendidik praktikan. Kedua, pentingnya rumusan deskripsi lebih lanjut tentang job description guru pamong pada masa pengenalan, pembimbingan dan eval-uasi praktikan didasarkan pada persoalan yang kerap terjadi pada kegiatan PPL. Ketiga, perlunya koordinasi antara LPTK dan sekolah secara simultan, kontinu dan intens dimana saling memberi hubungan timbal balik dalam upaya membentuk bibit calon guru yang profesional. Artikel ini di-tulis dengan menggunakan pendekatan library research dengan menelaah sejumlah literatur.Kata kunci : Praktek Pengalaman Lapangan, Manajemen Kurikulum, Model Pendidikan Guru